2020
DOI: 10.1038/s41598-020-64696-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk of arbovirus emergence via bridge vectors: case study of the sylvatic mosquito Aedes malayensis in the Nakai district, Laos

Abstract: Many emerging arboviruses of global public health importance, such as dengue virus (DenV) and yellow fever virus (YfV), originated in sylvatic transmission cycles involving wild animals and forest-dwelling mosquitoes. Arbovirus emergence in the human population typically results from spillover transmission via bridge vectors, which are competent mosquitoes feeding on both humans and wild animals. Another related, but less studied concern, is the risk of 'spillback' transmission from humans into novel sylvatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
2
7
1
Order By: Relevance
“…These observations could emphasize a crucial role of the midgut infection barrier and the salivary gland infection and escape barriers to limit the transmission of this virus for both lineages, whereas no impact was observed for the midgut escape barrier [ 41 , 42 ]. For the infection rate, these results contrasted with previous data obtained for other arboviruses such as DENV-1 and yellow fever virus (YFV; experiments conducted in Institut Pasteur, Paris) in Lao PDR [ 43 , 44 ]. For these flaviviruses, infection rates of Ae.…”
Section: Discussioncontrasting
confidence: 99%
“…These observations could emphasize a crucial role of the midgut infection barrier and the salivary gland infection and escape barriers to limit the transmission of this virus for both lineages, whereas no impact was observed for the midgut escape barrier [ 41 , 42 ]. For the infection rate, these results contrasted with previous data obtained for other arboviruses such as DENV-1 and yellow fever virus (YFV; experiments conducted in Institut Pasteur, Paris) in Lao PDR [ 43 , 44 ]. For these flaviviruses, infection rates of Ae.…”
Section: Discussioncontrasting
confidence: 99%
“…In the Lao PDR, a vector competence study has previously demonstrated a high transmission rate of DENV-1 by Ae. aegypti (transmission efficiency > 50% at 14 days post-infection) [50]. All these data thus emphasize the risk of DENV-1 epidemic re-emergence in the Lao PDR, especially during and after the rainy season.…”
Section: Discussionmentioning
confidence: 73%
“…Vector competence of Ae. aegypti from Lao PDR was investigated for DENV-1 and showed that 50% of the females orally exposed to the virus could transmit DENV-1 [ 52 ]. These data indicate a high efficiency of transmission of this serotype by Ae.…”
Section: Discussionmentioning
confidence: 99%